Effect of Problem-Based Learning Model on Learning Motivation in Quality Control Course - Josua Alexander Gultom; Windo Sinurat; Manaor Silitonga; Eliya Fatma Harahap; Abdurohim Abdurohim (Edumaspul: Jurnal Pendidikan, 2024)
This study is to evaluate the effectiveness of problem-based learning in increasing student learning motivation in quality control course at college in Lubuk Pakam, North Sumatra Province. The method approach used is quantitative research involving 40 college students as respondents. This research was conducted by providing teaching using problem-based learning, learning model for one semester, and then evaluating student learning motivation. Hypothesis testing uses simple regression analysis. The result showed that the implementation of problem-based learning model significantly increased students' learning motivation in quality control course. Students showed improvement in active engagement in learning, deeper conceptual understanding, and development of problem-solving skills. The findings highlight the importance of interactive and student-centered learning approaches in improving learning effectiveness in higher education.